Rebranding bread: a shopper marketing success story - Masterson, Chris (Henry Stewart Talks, 2016)
The case study looks at the extreme transformation of baked goods from being a key loss leader to a key value growth category in the grocery industry. Mr. Masterson elaborates on the role of appealing product innovation and marketing, and building the shopper’s in-store experience, in the revitalization of baked goods.